Efficacy and safety of anti-CGRP monoclonal antibodies for chronic migraine prophylaxis in patients treated with botulinum toxin A: A prospective monocentric study - Calogera Butera; Ilaria Cetta; Roberta Messina; Laura Zanandrea; Roberto Santangelo; Bruno Colombo; Massimo Filippi; Ubaldo Del Carro (SAGE Publishing, 2024)
Since the high burden of chronic migraine (CM), it is challenging to identify the best prevention treatment. Based on the preclinical evidence about the different therapeutic targets of onabotulinumtoxinA (BT-A), acting on C-fibers, and anti-CGRP monoclonal antibodies (mAbs), acting on Aδ-fibers, the rationale of using alternative or combining therapies has been hypothesized. Until now, the association of BT-A and mAbs has been poorly investigated. This study evaluated whether mAbs are effective and safe in CM patients previously treated with BT-A, either as an alternative or add-on treatment. We enrolled 47 patients: according to the response to BT-A treatment, patients were defined as non-responder (NR) and partial-responder (PR). NR were shifted to mAbs. PR were randomly divided into those who added mAbs therapy (PR-P) and those who shifted treatment (PR-S), interrupting BT-A. Clinical variables were collected at baseline, after three and six months. Study results evidenced the efficacy of mAbs in improving clinical outcomes in CM patients, with a better response in the PR group. No statistically significant differences in clinical changes were observed between PR-P and PR-S groups. No safety concerns were raised in combined treatments. Preventive prophylaxis with mAbs is effective, even in difficult to treat CM patients. Further studies, with larger samples, are needed to highlight a potential additive effect of combined therapies.